2003
DOI: 10.1046/j.1365-2044.2003.03123.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of a continuous oxygen consumption monitor in mechanically ventilated patients

Abstract: SummaryWe measured oxygen consumption using a new noninvasive modular metabolic monitor, M-COVX TM , in ventilated critically ill patients. Oxygen consumption was measured continuously as part of routine monitoring for up to 24 h following mechanical ventilation in 27 patients admitted to a general intensive care unit. We explored several possible sources of error. Most errors related to inaccurate tidal volume measurement, which resulted in rejection of a median 14% (interquartile range 8-34%) of data. Water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…We used a commercial device, based on the principle of indirect calorimetry to measure V O 2 in our patients; this system has the advantage of being noninvasive (requiring only a small connector at the circuit Y) and of providing continuous measurements of V O 2 . In our study we found a good reproducibility of the V O 2 measurements obtained during two different study phases; the system has been validated mainly by comparisons with the previous Deltatrac monitor, 14,28,29 showing a good reliability. Although the different inspiratory flow profiles have not been found to affect measurement reproducibility, 30 no data are available on the potential effect of different tidal volumes or respiratory rates.…”
Section: Discussionmentioning
confidence: 77%
“…We used a commercial device, based on the principle of indirect calorimetry to measure V O 2 in our patients; this system has the advantage of being noninvasive (requiring only a small connector at the circuit Y) and of providing continuous measurements of V O 2 . In our study we found a good reproducibility of the V O 2 measurements obtained during two different study phases; the system has been validated mainly by comparisons with the previous Deltatrac monitor, 14,28,29 showing a good reliability. Although the different inspiratory flow profiles have not been found to affect measurement reproducibility, 30 no data are available on the potential effect of different tidal volumes or respiratory rates.…”
Section: Discussionmentioning
confidence: 77%
“…[12][13][14] Data were continuously collected by dedicated software (Collect S5, GE Health Care, Finland). Body temperature was monitored by a rectal probe and kept normal by heating pads (38.5-39°C in pigs).…”
Section: Preparation and Data Collectionmentioning
confidence: 99%
“…Measurements of oxygen consumption (VO 2 ) and CO 2 production (VCO 2 ) were also provided by the monitor (COVX Module, GE Health care, Finland). [12][13][14] Data were continuously collected by dedicated software (Collect S5, GE Health Care, Finland). 12…”
Section: Preparation and Data Collectionmentioning
confidence: 99%
“…The NICOM uses bioreactance to estimate cardiac index by interpreting signal from adhesive sensors attached to the patient's torso, and has been validated in prior studies (12). The GE compact anesthesia monitor measures V : O 2 using a pneumotachograph and a rapid paramagnetic analyzer attached in-line with the ventilator tubing, and has been validated in critically ill, mechanically ventilated patients (10,11,13)…”
Section: Data Collectionmentioning
confidence: 99%